2008
DOI: 10.1128/cvi.00358-07
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Histoplasma capsulatum Antigen in Panamanian Patients with Disseminated Histoplasmosis and AIDS

Abstract: Histoplasmosis is a common endemic mycosis in the Americas, often causing severe disease in patients with AIDS. Antigen detection has become an important method for rapid diagnosis of histoplasmosis in the United States but not in Central or South America. Isolates from patients in the United States are predominantly found to be class 2 isolates when typed using the nuclear gene YPS3, while isolates from Latin America are predominantly typed as class 5 or class 6. Whether infection with these Latin American ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…The H. capsulatum isolates were IU-CT (3, 11) and 94-255 (8). Genotyping using YPS3 (1,9) showed that the 94-255 isolate did not express YPS3 and, thus, was a class 1 strain, whereas the IU-CT isolate expressed YPS3, which is characteristic for class 2 (Fig. 1A), the predominant type in North America (20).…”
mentioning
confidence: 99%
“…The H. capsulatum isolates were IU-CT (3, 11) and 94-255 (8). Genotyping using YPS3 (1,9) showed that the 94-255 isolate did not express YPS3 and, thus, was a class 1 strain, whereas the IU-CT isolate expressed YPS3, which is characteristic for class 2 (Fig. 1A), the predominant type in North America (20).…”
mentioning
confidence: 99%
“…In AIDS patients with histoplasmosis, antigenemia was present in 95% in the MVista EIA compared with 87% in the original EIA. Recently, these fi ndings have been extended to Panamanian patients with AIDS complicated by PDH [21]. Antigenuria and antigenemia were detected in 95% of the Panamanian cases compared with 100% and 92%, respectively, of the US cases.…”
Section: Accuracy Of the Mvista Histoplasma Antigen Eiamentioning
confidence: 87%
“…For example, in the quantitative MVista Histoplasma antigen enzyme immunoassay (EIA), among patients with AIDS and progressive disseminated histoplasmosis (PDH), antigenuria was detected in 95 to 100% compared to 92 to 95% for antigenemia (1,3). Previously, we noted improvement in the sensitivity for detection of antigenuria after ultrafiltration (2).…”
mentioning
confidence: 99%
“…Second, urine may not be available in patients with renal failure. Third, antigenuria levels early in the infection often are above the reportable range of the MVista Histoplasma antigen EIA (1,3). Clearance of antigenemia may provide a better marker for response to therapy in such cases.…”
mentioning
confidence: 99%